Modeling and characterizing errors in satellite and reanalysis precipitation estimates using a two-step decomposition procedure - Zhehui Shen; Mingze Ding; Ruochen Huang; Hao Wu; Bin Yong (Journal of Hydrology, 2026)

11‐Year Solar Cycle Signature in the Summer Stratospheric Temperature Over the Pacific - Ruochen Wang; Liang Zhao; Haoxin Yao; Xinyong Shen; Jingsong Wang; Ziniu Xiao; Jinjuan Liu; Weiguo Zong (International Journal of Climatology, 2026)
Although previous studies have identified a quasi‐11‐year solar cycle signal in sea surface temperature and tropopause temperature over the Pacific, the existence of a solar cycle signal in the Pacific stratosphere remains underexplored. This study analyses temperature data from various levels of the Pacific stratosphere during June, July and August (JJA) from 1980 to 2022. Through regional averaging, vertical integration and power spectrum analysis, we identify a significant influence of solar activity on EOF2 of JJA‐mean 50 hPa temperature over the Pacific. This response is characterized by a meridional tripolar distribution, with cold anomalies over the equator and warm anomalies in the subtropics. Mechanism analysis shows that during high solar activity years (HSY), enhanced radiative heating in the subtropical stratosphere over the Pacific reduces the meridional temperature gradient, which weakens zonal winds according to the thermal wind principle, thus facilitating planetary wave propagation. This leads to increased wave activity, which strengthens the Brewer‐Dobson (BD) circulation. More ozone is transported from the equator to the subtropics, raising ozone concentrations, absorbing more solar ultraviolet (UV) radiation and causing warming in the subtropics. In contrast, the equatorial region experiences cooling, resulting in a meridional tripolar structure in the JJA‐mean 50 hPa temperature over the Pacific. Using the CMIP6 hist‐sol experiment, we analyse the key physical processes under the influence of solar activity and reveal how solar activity impacts ozone distribution through planetary waves and the BD circulation, ultimately affecting temperature.

Overcoming acidic constraints: A bio-inspired cu-bilirubin nanozyme with superior neutral-pH peroxidase and laccase-like activities for selective sensing and removal of formaldehyde and pyrogallic acid - Ruochen Duan; Xiaohui Hao; Ao Shen; Panqing Zhang; Zeyu Zhang; Xuebing Wang; Long Chen; Qingyang Fan; Jiahao Wang; Yunxu Yang (Chemical Engineering Journal, 2026)

Crystal-facet regulation of SnO₂ {221} and {110} for selective detection of dimethyl carbonate and H2 gases in battery thermal runaway - Xun Shen; Aijun Yang; Ruochen Ding; Kehan Bo; Jifeng Chu; Pengxu Chen; Chenhui Li; Hongye Yuan; Huan Yuan; Mingzhe Rong; Xiaohua Wang (Chemical Engineering Journal, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

Saline water treatment coupled with carbon dioxide capture by bipolar membrane electrodialysis in a continuous feed-bleed mode: The effect of proton leakage - Tianyi Chen; Ruochen Shen; Hongshuo Sun; Jingtao Bi; Mengmeng Sun; Shizhao Wang; Xiaofu Guo; Wenhao Li; Jianlu Liu; Yingying Zhao (Chemical Engineering Journal, 2024)

Bipolar membrane electrodialysis integrated with in-situ CO2 absorption for simulated seawater concentrate utilization, carbon storage and production of sodium carbonate - Jingtao Bi; Tianyi Chen; Yue Xie; Ruochen Shen; Bin Li; Mengmeng Sun; Xiaofu Guo; Yingying Zhao (Journal of Environmental Sciences, 2024)

A comprehensive investigation of three long‐term precipitation datasets: Which performs better in the Yellow River basin? - Ruochen Huang; Bin Yong; Fan Huang; Hao Wu; Zhehui Shen; Da Qian (International Journal of Climatology, 2024)
The fifth generation European Centre for Medium‐Range Weather Forecasts Reanalysis on global land surface (ERA5‐Land), the Multi‐Source Weighted‐Ensemble Precipitation (MSWEP), and the Climate Hazards Group Infrared Precipitation with Stations (CHIRPS) are three representative precipitation estimates with quasi‐global coverage, high‐resolution and long‐term record. This study concentrates on investigating, for the first time, the long‐term spatiotemporal accuracy and regional applicability of these precipitation estimates at a daily scale in the Yellow River basin (YRB) using 39 complete years of data record (1981–2019), with a special focus on their capability on monitoring the extreme precipitation events with short duration and the continuous heavy precipitation events. Results indicate that MSWEP generally performs better than ERA5‐Land and CHIRPS in almost all seasons and subregions, with the highest Pearson correlation coefficient and critical success index, lowest root mean square error and false alarm ratio. ERA5‐Land presents a severe overestimation of precipitation amount, particularly in the plateau climate region (BIAS = 52.27%), but well reflects its spatial–temporal patterns in the YRB. As for the detecting capability, MSWEP shows the best accuracy in detecting extreme precipitation, particularly in maximum consecutive 5‐day precipitation (RX5day). The MSWEP better represents the spatial distribution of maximum 1‐day precipitation and maximum consecutive 5‐day precipitation in the YRB, but it shows a significant overestimation in zone Southern Qinghai. MSWEP and CHIRPS have better performance of temporal variation consistency in annual precipitation with ground reference than ERA5‐Land, while ERA5‐Land performs well in capturing extreme precipitation temporal variation, especially for continuous heavy precipitation events. This study can provide useful guidance when choosing long‐term precipitation products for hydrometeorological applications and climate‐related studies in the YRB.

Fabrication of a porous Urea@MIL-100(Fe)/CI-MCC/SA hydrogel for All-In-One adsorption, removal and fluorescence monitoring of nitrite - Xiaohui Hao; Ao Shen; Ruochen Duan; Panqing Zhang; Lingwei Xue; Xiuqing Zhao; Xuebing Wang; Xue Li; Yunxu Yang (Journal of Hazardous Materials, 2024)

Simple method for visual detection of nitrite using fluorescence and colorimetry by poly (tannic acid) nanoparticles - Xiaohui Hao; Ao Shen; Mengwen Li; Ruochen Duan; Lala Hou; Xiuqing Zhao; Ziqi Li; Yongwei Zhao; Panqing Zhang; Xuebing Wang; Xue Li; Yunxu Yang (Analytica Chimica Acta, 2023)

Housing market capitalization of environmental risk: evidence from the Tianjin explosion - Kaiyang Chen; Gary D. Ferrier; Ruochen Jiang; Zhiyang Shen (Environmental Science and Pollution Research, 2022)

Profiling of bacterial transcriptome from ultra‐low input with MiniBac ‐seq - Tianmin Wang; Ping Shen; Ruochen Chai; Yihui He; Jintao Liu (Environmental Microbiology, 2022)
There is a lack of appropriate methods for preparing bacterial RNA‐seq library with ultra‐low amount of RNA. To address this issue, we developed miniBac‐seq, a strand‐specific method for high‐quality library construction from sub‐nanogram of total RNA, which is 100‐fold lower than the current benchmark kit and dramatically reduces preparation cost ($28 + $15 × samples). We further demonstrated the high sensitivity of miniBac‐seq via detecting more than 500 genes from amount of total RNA equivalent to that of a single bacterial cell. Finally, we profiled the transcriptome of growth‐arrested bacteria in isogenic culture of Escherichia coli . This subpopulation of bacteria is generally low in abundance but is a potent reservoir of antibiotic persistence, and their gene expression has been largely unknown due to technical limitations. Using miniBac‐seq, we identified potential molecular driver towards arrested growth as well as antibiotic tolerance. Our method thus expands the capacity to quantify bacterial transcriptome in situ, which is useful to the understanding of bacterial physiology and regulation in their native contexts.

Application of carotenoid to alleviate the oxidative stress caused by phenanthrene in wheat - Yu Shen; Jinfeng Li; Shengnan Shi; Ruochen Gu; Xinhua Zhan; Baoshan Xing (Environmental Science and Pollution Research, 2019)